(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the importance of teaching students using a creative approach in teaching English, as well as the current interest in teaching and learning foreign languages in educational institutions and non-state higher education institutions in our country, with the help of modern technologies, new A comparative analysis of fundamental, linguo-sociocultural, and communicative methods was conducted using methodologies. The role and importance of teaching students using a creative approach in the educational process were scientifically demonstrated and explained.